2012
DOI: 10.3390/molecules171214821
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Comprehensive Evaluation of (Poly)phenolic Compounds in Pomegranate (Punica granatum L.) Juice by UHPLC-MSn

Abstract: The comprehensive identification of phenolic compounds in food and beverages is a crucial starting point for assessing their biological, nutritional, and technological properties. Pomegranate (Punica granatum L.) has been described as a rich source of (poly)phenolic components, with a broad array of different structures (phenolic acids, flavonoids, and hydrolyzable tannins) and a quick, high throughput, and accurate screening of its complete profile is still lacking. In the present work, a method for UHPLC sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
174
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(201 citation statements)
references
References 50 publications
24
174
1
2
Order By: Relevance
“…This data showed that the nine cultivars studied presented different polyphenols profiles. As already reported in the literature, hydrolyzable tannins are the most abundant antioxidant polyphenolic compounds in pomegranate juices [50,51] and include pedunculagin (11,12,15), punicalin (10), punicalagin (17), HHDP glucoside (7) and ellagic acid (3,4,5,6,13,14). The highest number of hydrolyzable tannins was detected in CG8, Cis 127, and Wonderful 1 (17 compounds).…”
Section: Identification and Quantification Of Phytochemicals Compoundmentioning
confidence: 67%
See 4 more Smart Citations
“…This data showed that the nine cultivars studied presented different polyphenols profiles. As already reported in the literature, hydrolyzable tannins are the most abundant antioxidant polyphenolic compounds in pomegranate juices [50,51] and include pedunculagin (11,12,15), punicalin (10), punicalagin (17), HHDP glucoside (7) and ellagic acid (3,4,5,6,13,14). The highest number of hydrolyzable tannins was detected in CG8, Cis 127, and Wonderful 1 (17 compounds).…”
Section: Identification and Quantification Of Phytochemicals Compoundmentioning
confidence: 67%
“…Comparing our results with Li et al [70], who had studied 10 Chinese cultivars, higher ranges were found, namely: 0.70-15.93 mg/l. Thirteen different flavonoids belonging to five subclasses of non-colored flavonoids (flavan-3-ols, flavonols, flavanones, flavones, and dihydrochalcones) were identified, all previously reported in pomegranate juice [50,51]. The highest number of non-colored flavonoids compounds (11 compounds) was detected in the juice of Cis 127.…”
Section: Identification and Quantification Of Phytochemicals Compoundmentioning
confidence: 74%
See 3 more Smart Citations